Análisis del estándar IEEE 802.16m (WIMAX 2) y su factibilidad de implementación en el Ecuador. - Poma Ordóñez, Guido Alejandro (2014)
The present project was performed as a systematic analysis of the technology IEEE 802.16m also called "Wimax 2" and the possibility to make implementations of this technology in Ecuador. This standard allows the transmission of information at high data rates and high speed mobility. The IEEE 802.16m standard is part of the technologies known as “Wimax” and it’s listed as a fourth generation technology (4G) jointly with LTE-Advanced. The feasibility analysis contains the next parts: regulatory framework, market research, equipment selection and the initial investment. The present study is performed in Loja city with the intention of implement an Internet service provider. Considering manufacturers of Wimax technology, the 3.5 GHz frequency is utilized. The Market research involves the design and implementation of an Internet service provider, we look the demand estimation, user's projection and the services to offer. The technical analysis determines the nodes location, propagation losses and coverage areas. There is established locate two base stations; the first is located on Punzara and second base station on San Cayetano Alto. The standard used is IEEE 802.16d-2004. The used provider is Airspan. The telecommunications room is located on San Cayetano Alto. Finally the initial inversion is performed with the external equipment and the internal equipment.